The New Challenges of the Technification of Work: Managing Technostress Through Positive Organizational Psychology - Cuervo Carabel, Tatiana; Meneghel, Isabella; Orviz Martínez, Natalia; Arce García, Sergio (ALOMA. Revista de Psicologia, Ciències de l'Educació de l'Esport, 2020)
The introduction of new and changing technologies has led to changes in all areas of society, and the world of work is no exception. This had created a need for an analysis and reformulation of habits and actions related to workplace health and safety. "Technostress" has emerged as one of the risks associated with the increasing use of information and communication technologies. The aim of this work is to analyze the effectiveness of positive psychosocial interventions aimed at technostress management. To do this, the two concepts are analyzed via a case study. The study begins with an assessment of technostress among the management staff of a service company. Based on the results of this initial assessment, a range of ongoing Positive Psychology interventions were designed and implemented. It is concluded that Positive Organizational Psychology can be an effective tool for technostress management. The main constraints of this work would be associated with the size of the sample, which does not allow the generalization of the results. Nonetheless, it opens a door to a new research paradigm to delve deeper into the issue of technostress management from the field of Positive Psychology, which a connection that to date has received scanty theoretical attention.
Keywords: Technostress; Positive Organizational Psychology; technology; safety and health; Emerging; Scopus